THE EFFECTIVENESS OF DANCE EXTRACURRICULARS IN ENCOURAGING PROGRESS ACADEMIC AND NON-ACADEMIC STUDENTS AT THE LEADING AL- AZHAR HIGH SCHOOL IN MEDAN - Tisya Dwi Khanaya; OK Mhd Rayyan Athaya; Muhammad Fayyaz Algifari; Ratu Azura Saragih; Indah Astriani; Trivana Rija Bangun (CV. RADJA PUBLIKA, 2024)
This research is a study of the effectiveness of extracurricular dance, which is a form of activity that is currently scheduled and is a routine activity every Monday and Wednesday at Al-Azhar Superior High School, Medan. The aim is to examine the effectiveness of extracurricular programs in advancing academic and non-academic students at Al-Azhar Medan Superior High School. The research method chosen was a qualitative descriptive approach by conducting a survey of 4 out of 35 students who played an active role in participating in dance extracurricular activities. The research results state that participation in extracurricular activities has a positive and significant impact on increasing academic achievement, developing non-academic skills such as memory, teamwork, and focus for students who are active in implementing them. Apart from that, it also describes increased learning motivation and a greater sense of involvement in activities in the school environment. This explains the importance of extracurricular programs as a means of encouraging the development of the achievements of every student who is active in their implementation.